(untitled) (International relations and international law Journal, 2016)
Due to the lack of qualified specialists among graduates of educational institutions and their apartness from the real production that employers own, having studied the German experience, Republic of Kazakhstan started to establish the dual education system. But in the process of introducing the German experience educational institutions along with Kazakhstan employers have discovered problematic issues that can be solved via submitting changes to Republic of Kazakhstan’s legislation. The article analyzes the current tax and labour legislaton, and the laws in the field of education when applying the dual education system as well, and also contains recommendations for adapting to the dual education system in Kazakhstan.